Vibration energy harvesting using single and comb-shaped piezoelectric beam structures: modeling and simulation - Diyana, N. H.; Abdul Muthalif, Asan Gani; Fakhzan , M. N.; Nordin, Anis Nurashikin (Elsevier, 2012)
Of late, many have shown great interests in the area of energy harvesting or energy scavenging. Researchers have been venturing into methods that can generate acceptable level of voltage since decades ago. In line with the spirit of green technology, energy harvesting will be a major contributor towards saving our environment in near future. Vibration energy harvesting, specifically, is getting more and more attention nowadays. With the abundant sources, this type of energy harvesting can generate desired voltage to power any low power devices and wireless sensor; and subsequently high power devices in the future. In this research, unimorph piezoelectric energy harvester is chosen to harvest wideband mechanical energy. The derivation of the mathematical modelling is based on the Euler-Bernoulli beam theory. MATLAB and COMSOL Multiphysics software are used to study the influence of the structure in generating output voltage due to base excitations. Finally, the results of the frequency response are displayed in the form of voltage within frequency range of 0 to 3500 Hz, at which the comb-shaped piezoelectric beam structure shows better performance as there exist more natural frequencies in the specified range of frequency.